Immunogenicity and safety of an accelerated hepatitis E vaccination schedule in healthy adults: a randomized, controlled, open-label, phase IV trial. (September 2019) - Chen, Z.; Lin, S.; Duan, J.; Luo, Y.; Wang, S.; Gan, Z.; Yi, H.; Wu, T.; Huang, S.; Zhang, Q.; Lv, H.
Abstract: Objectives: This study aimed to evaluate the immunogenicity and safety of a hepatitis E (HE) vaccine using an accelerated vaccination schedule (vaccine doses at 0, 7 and 21 days). Methods: A total of 126 participants aged ≥18 years were randomly assigned to receive the hepatitis E virus vaccine in either the accelerated group (0, 7 and 21 days) or the routine group (0, 1 and 6 months). Serology samples were obtained at 0, 21, 28 and 51 days, and 7 months in the accelerated group, or 0, 1, 2 and 7 months in the routine group after the first vaccine injection. Adverse events (AEs) reported during the whole study were analysed. Results: A total of 126 participants were randomized, 63 for each group. Sixty-two participants in the accelerated group and 63 in the routine group received at least one dose of vaccine; 57 and 63 participants received all three doses and were included in per-protocol set, respectively. In the per-protocol population, at 1 month after the last dose (accelerated group at 51 days versus routine group at 7 months), the seropositive rates were both 100% (57/57 and 63/63, respectively), and the geometric mean concentrations (GMCs) were 8.51 WHO units/mL (95% CI 6.73–10.76) in the accelerated group and 9.67 WHO units/mL (95% CI 7.67–12.20) in the routine group. The ratio of the accelerated group GMC to the routine group GMC was 0.88 (95% CI 0.61–2.17, lower limit of 95% CI > 0.5), indicating that the accelerated vaccination schedule was non-inferior to the routine one. The overall incidence rates of solicited AEs in the accelerated and routine groups were 32.26% (20/62) and 30.16% (19/63), respectively (p 0.800). Most AEs were moderate. Conclusions: An accelerated schedule is safe and provides protective antibodies in a shorter time compared with the routine schedule. The accelerated schedule should be recommended to adults who are travelling on short notice to an HE-endemic area or during an HE outbreak (Clinical Trial Registration. NCT03168412)